Análise do desempenho do concreto de cimento Portland com e sem substituição parcial do cimento por cerâmica vermelha ou metacaulim submetido a altas temperaturas - Glayson Barbosa Sampaio (2022)
Exposure to high temperatures, such as in a fire situation, contributes to the degradation of concrete structures, which compromises the durability of the building. Therefore, under high temperatures the carrying capacity of a building may be compromised, which may lead to structural collapse. The partial replacement of Portland cement by supplementary cementitious materials (SMC) in concrete can contribute to better performance in a fire situation. Thus, it is pertinent to understand the behavior of concrete after fire situations, in order to investigate its performance and the resilience of buildings. And thus, contribute to the analysis of the safety and durability of a concrete structure when subjected to a fire situation. The objective of this work was to analyze the influence of the use of Metakaolin and Red Clay as supplementary cementitious materials on the performance of concrete subjected to high temperatures from natural and fire pattern simulations. To this end, a reference dosage of usual concrete for infrastructure works will be developed. From this, six more concretes were made with partial replacement of Portland cement by 5%, 10% and 20% of Metakaolin or Red Clay. The mechanical characterization of the specimens occurred through tests of compressive strength and dynamic elastic modulus. Durability parameters were evaluated through bulk electrical resistivity, absorption and void ratio. The concretes REF, MET20 and CV20 were subjected to high temperatures in the oven, ISO 834:1975 standard curve, and in the container, natural fire curve. The results shows that the partial replacement of cement by Metakaolin or Red Clay contributed to improve the mechanical properties and durability of the concrete produced. Exposure to high temperatures promoted the degradation of concrete properties. The MET20 concrete was the one that showed greater resilience to fire simulations.